2022
DOI: 10.46729/ijstm.v3i3.509
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening And Antibacterial Activity Test Of Ethanol Extract Of Jengkol Leaves (Archidendron Pauciflorum Benth.) I.C. Nielsen Against Staphylococcus Epidermidis And Propionibacterium Acnes

Abstract: Skin disease was a disease that attacked the surface of the body, and was caused by various agents, one was bacteria. One of the plants that had antibacterial activity was jengkol leaf (Archidendron pauciflorum Benth.) I.C. Nielsen because it contained compounds that had antibacterial properties that had previously been studied by other researchers against Staphylococcus aureus and Escherichia coli bacteria. So that researcher was interested in researching on the antibacterial activity of jengkol leaves (Archi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
7
0
3
Order By: Relevance
“…may play a significant role in the protection of A. pauciflorum against phytopathogens. Although the host also reported having antibacterial activity against pathogens [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…may play a significant role in the protection of A. pauciflorum against phytopathogens. Although the host also reported having antibacterial activity against pathogens [20].…”
Section: Discussionmentioning
confidence: 99%
“…The phytochemical profile of endophyte extract was also similar to the extract derived from their host. All these compounds are also found in the leaf and fruit peel extract of A. pauciflorum [20,24]. Previous studies reported that phytochemicals were also commonly found in the crude extract of endophytic bacteria isolated from medicinal plants [25][26].…”
Section: Discussionmentioning
confidence: 99%
“…If the solution foams, add 1% HCl and wait 10 minutes; if the foam remains, the extract includes saponins. Flavonoid test, specifically 0.5 grams of a papaya leaf extract from the extraction results added with 1-2 ml of hot water and a small amount of magnesium (Mg) powder and shaken until mixed; then added 4-5 drops of 37% HCl and 4-5 drops of 95% ethanol% and shaken until mixed [14]. Observing the color change in the extract solution, the extract contained flavonoids if a red, yellow, or orange hue occurred.…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…Two hours of maceration with 20 mL of n-hexane, followed by filtration. The filter was evaporated, and the remaining substance was dripped with Libermann-Bouchart reagent (Nasution et al, 2022).…”
Section: Steroid / Triterpenoid Examinationmentioning
confidence: 99%